Adding Proximity Sensing Capability to Tactile Array Based on Off-the-Shelf FSR and PSoC - Castellanos-Ramos, Julián; Trujillo-León, Andrés; Navas-González, Rafael Jesús; Barbero-Recio, Francisco; Sánchez-Durán, José Antonio; Oballe-Peinado, Óscar; Vidal-Verdú, Fernando (IEEE, 2020)
Tactile sensors have been incorporated into robots to help in many tasks, such as preventing damage to humans in collaborative works or assistance or in dexterous manipulation. Proximity sensors are also common in robotics and are proposed to implement pretouch in multimodal realizations. Many tactile sensors are based on off-the-shelf force-sensing resistors (FSRs). The parasitic capacitance associated with the electrodes of the FSR can be exploited to measure proximity. Moreover, it is possible to implement both force and proximity signal acquisition with a single chip. This article presents a multimodal proximity and tactile patch based on commercial FSR plus a programmable system on chip (PSoC). The ability to measure proximity is achieved without adding any extra element. Discussions about key design issues as well as results that show the performance of the sensor patch are presented. As proximity sensing array, the range is in the order of the size of the electrodes, and it depends on the properties of the object nearby, as expected. The best performance is observed for conductive objects. Therefore, this approach is especially interesting in human–robot interaction tasks, such as shaping robotic hands or grippers around the human body. Furthermore, dielectric objects are also detected, so it can also be used to implement pretouch in manipulation tasks.
Keywords: Tacto; Detectores; Multimodal sensors; Pretouch; Programmable system on chip (PSoC); Proximity sensors; Tactile sensors